O núcleo de prática jurídica da PUC Goiás como instrumento de desenvolvimento social e acesso à justiça - Freitas, Breno Delfino Amaral (2024)
Over the years to date, there has been an expansion in the occupation of new spaces that constitute the Rights Guarantee System, mainly since the promulgation of the Federal Constitution of 1988, which calls for the implementation of Law, necessary for the materialization of access to Justice. A place, par excellence, for the affirmation and guarantee of human rights and social development refers to the Legal Practice Centers (NPJ), linked to Universities and other Higher Education Institutions which, with the complexity of social life and the daily violation of rights, has been called upon to respond to the most diverse demands, requesting the contribution of other areas of knowledge, in addition to the area of Law. Based on this, this dissertation proposes to investigate the contribution of the Legal Practice Center of the Pontifical Catholic University of Goiás (PUC Goiás) in achieving access to justice, from the perspective of social development. The work is organized into three chapters: the first addresses the theme of access to justice in an expanded conception, reviewing its historical construction process in the global and Brazilian context, contemplating, in an intertwined and organic way, the affirmation and guarantee of rights; the second chapter deals with the formation and functioning of the Legal Practice Centers, as well as the pedagogical and social aspects of these university units; the third and final chapter addresses the formation and functioning of the Legal Practice Center at PUC Goiás, also dedicating itself to the presentation and discussion of data seized in the investigation process. The method used in the approach is dialectical. The expected result was found, pointing out the problems and it was concluded that given the limitations of the Public Defender's Office of the State of Goiás and the activity of legal and pro bono law, the Legal Practice Center of PUC Goiás meets an important economically vulnerable demand , contributing substantially to breaking down barriers to access to justice in the Municipality of Goiânia. The provision of legal assistance to people with low economic income contributes to the student's education, in addition to promoting reciprocal integration between the University and the Community. It represents a way of promoting social emancipation, citizenship and the effectiveness of human rights